Removal of Reactive Black 5 (RB5) Dye from Aquatic Solution by Using of Adsorption onto Synthesized SodiumAlginate Magnetic Beads - H vahedi (سلامت و محیط, 2011)
"nBackground and Objectives: Industrial wastewater included the dyes one of the important sources of environmental pollution, that founded in loom wastewater which are harmful for human health and environment. Therefore, the purpose of this research was investigated removal of RB5 dye from aquatic solution by using of adsorption onto synthesized magnetic sodium alginate beads."nMaterial and Methods: At first, synthesized magnetic sodium alginate beads. Then, acquired beads optimum dosage equal to 18 g/100CC, with constant other parameters. The effect of pH, contact time and initial RB5 dye concentration was studied at the constant of beads (18 g/100CC)."nResults: Results showed that removal efficiency was decreased by increasing of initial RB5 dye concentration. Also the results showed the removal efficiency was increased by increasing of adsorbent dose and contact time. The results showed data were explained acceptably by Langmuir isotherms and pseudo-second-order kinetics models respectively."nConclusion: The results showed that removal of RB5 dye from aqueous solution by using of magnetic sodium alginate beads can be done cheaper and effective.